2013
DOI: 10.2147/dmso.s44477
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome and prognostic indices in patients with hyperglycemic emergencies

Abstract: ObjectiveThe objective of this study is to assess the treatment outcomes in patients with hyperglycemic emergencies and to ascertain the factors associated with outcome, with emphasis on the determinants of outcome.MethodA total of 105 patients admitted to the Accident and Emergency unit, who fulfilled the criteria for hyperglycemic emergencies, were selected. The information extracted included sociodemographic, clinical, and laboratory data, as well as hospitalization outcome.ResultsOf the 105 subjects that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
3
16
3
Order By: Relevance
“…HHS was the major HE case. This nding goes in line with studies from Nigeria and Taiwan (15,(24)(25)(26)(27) but stands against a study reported that DKA was the commonest HE (22). The higher prevalence of HHS in our study might be explained by the fact that the majority of the study participants were T2DM patients, and that HHS often raids patients with uncontrolled T2DM (28).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…HHS was the major HE case. This nding goes in line with studies from Nigeria and Taiwan (15,(24)(25)(26)(27) but stands against a study reported that DKA was the commonest HE (22). The higher prevalence of HHS in our study might be explained by the fact that the majority of the study participants were T2DM patients, and that HHS often raids patients with uncontrolled T2DM (28).…”
Section: Discussionsupporting
confidence: 90%
“…The median length of hospital stay in our study was 7 days. Even though this is shorter than the ndings of studies from Nigeria and Colombia (5,24,25), it still is longer than the reports from Jimma and South…”
Section: Discussionmentioning
confidence: 64%
“…21,22,10,12 . With better understanding of the pathophysiology of DKA and improvements in treatment, outcome is improving 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…DKA is prone to occur in patients with Type 1 diabetes (T1DM) spontaneously [3], yet several studies suggested that each type of diabetes may be associated with DKA, and more DKA occurs in Type 2 diabetes (T2DM) [3]. Previous researches on DKA were often conducted in developed countries such as Europe, America, or Japan [4][5][6], nevertheless so far research data of patients with HEs from mainland China were limited, especially on the overall precipitants, clinical features, treatment outcomes and risk factors.…”
Section: Introductionmentioning
confidence: 99%